Comportamento de novilhas gir e girolandas leiteiras em sistema silvipastoril no semi-árido sergipano - Jesus, Roseane Santos de (2009)
The climatic conditions affect the dairy cattle acting, mainly in tropical areas. The knowledge of the functional relationships between the animal and the environment allows to adopt procedures that increase the milk exploration efficiency. Then, the present work had as objective evaluates the adaptive behavior of different genetic groups, in Silvopastoral system , in rainy days and drought. The experiment was driven in Fazenda Acauã, in Nossa Senhora da Glória/SE, in September and October of 2008. The experimental delimitation was entirely casualized, with three treatments (Gir, 1/2 Dutch-gir and 3/4 Dutch-gir) and four repetitions. The analyzed parameters were during the day on grazing, rumination and inactivity. It was also evaluated the time in which the heifers were stood up or lied down and the place: in the shadow and in the sun. The medium data of the grazing activities, position and place were submitted to analysis of variance. The comparison of the averages was made through the Tukey test at the level of 5% of probability, for analysis of the data it was used the SAS program (Statistical Analysis System 2002). The pasture of the area is varied with trees, bushes, herbaceous and prevalence of grassy Urochloa (Urochloa mosambicensis), which compose the Caatinga. There was a tendency of the animals spend more time (p < 0,05) grazing at that time rainy day than in the drought, except for the Gir heifers. The 1/2 Dutch-gir heifers presented more grazing time, differing significantly of Gir at that rainy time. On drought, the 1/2 Dutch-gir heifers grazed more than the 3/4 Dutch-gir heifers. When is analyzed the inactivity time, this is perceived that, in it drought, the average of the inactivity time was greater (p<0,05) that at the time rainy. There wasn´t time in inactivity differing (p>0,05) in rainy days among the 1/2 Dutch-gir heifers and 3/4 Douch-gir. While on drought the 3/4 Dutch-gir heifers presented more (p < 0,05) time in inactivity differing significantly of the 1/2 Dutch-gir heifers, however there weren't significant differences among the Gir heifers. As for the time of rumination, it was verified that on drought the times were larger (p < 0,05). Regarding the posture, the heifers stayed on foot for less (p < 0,05) time. As for the position and place the gir heifers stayed more time (p < 0,05) on foot in the sun than the 3/4 Dutch-gir heifers, and they didn't differ significantly of the 1/2 Dutch-gir heifers. Regarding the lied down position and in the sun, the 1/2 Dutch-gir heifers spent more time (p < 0,05) differing statically of the others. The animals spent more time (p < 0,05) on foot (resting or ruminating) and lying down (resting or ruminating) under the sun at drought. The species Gir following by the 1/2 Dutch-gir are the more suitable genetic groups to hot areas as the semi-arid, in the Silvopastoral system. The larger the degree of Dutch blood in the animals the less suitable these animals are to hot areas as the semi-arid.